Character Building in Contemporary Islamic Education and the Impact of Rauḍah Al Aṭfal Teacher Character Values Implementation in Rauḍah Al Aṭfal (RA) Muslimat Nahdlatul Ulama’ (NU) 1 Dinoyo Malang City - Sudirman Sudirman; Hayat Hayat (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The aim of this research is to gain a holistic understanding of: First, what are the impacts of the RA teachers’ character values implementation in RA Muslimat NU 1 Dinoyo, Malang City. Second, how to build RA teachers’ character in RA Muslimat NU 1 Dinoyo, Malang City in Contemporary Islamic education. Based on the desired objective, this is a case study using qualitative approach, that points out the importance of building RA (rauḍah al aṭfal) teachers’ character. Based on the dimension that seeks to understand the micro-subjective dimension that has dialectic relationship with the macro-subjective dimension , the paradigm used is Phenomenology. Ontologically, the paradigm understands that reality is complex and holistic. There are 16 pillars of Educators/Kindergarten Teachers’ Character Builder, namely: affection, appreciation, space Provision for Self Development, trust, cooperation, mutual sharing, mutual motivation, mutual listening, positive mutual interaction, mutual moral value embedment, mutual sincere reminder, mutual enthusiasm giving, mutual self potential seeking, mutual teaching with humility, mutual inspiration, mutual respect for diversity.